COMPARISON OF OUTCOME BETWEEN LOW AND HIGH THORACIC TRAUMA SEVERITY SCORE IN BLUNT TRAUMA CHEST PATIENTS - Subhani, Shahzadi Samar; Muzaffar, Mohammad Sultan; Khan, Muhammad Imtiaz (Journal of Ayub Medical College Abbottabad, 2014)
Background: Blunt chest trauma is second leading cause of death among trauma patients. Early identification and aggressive management of blunt thoracic trauma is essential to reduce the significant rates of morbidity and mortality. Thoracic trauma severity score (TTS) is a better predictor of chest trauma related complications. The objective of the study was to compare outcomes between low and high thoracic trauma severity score in blunt trauma chest patients. Methods: A cross sectional descriptive study was carried out in public and private sector hospitals of Rawalpindi, Pakistan from 2008 to 2012 and 264 patients with blunt trauma chest who reported to emergency department of the hospitals, within 48 hrs of trauma were recruited. All patients were subjected to detailed history and respiratory system examination to ascertain fracture ribs, flail segment and hemopneumothorax. Written and informed consent was taken from each patient. Permission was taken from ethical committee of the hospital. Results: The patients with blunt chest trauma had an array of associated injuries; however there were 70.8% of patients in low TTS group and 29.2% in high TTS group. Outcome was assessed as post trauma course of the patient. Outcome in low and high TTS group was compared using Chi square test which shows a significant relationship (p=0.000) between outcome and TTS, i.e., outcome worsened with increase in TTS. Conclusion: It is concluded that there is a significant relationship between outcome and thoracic trauma severity. Outcome of the patient worsened with increase in thoracic trauma severity score. Keywords: Blunt chest trauma, Poly trauma, Thoracic trauma severity score, TTS, Pakistan